2016
DOI: 10.1139/cgj-2016-0057
|View full text |Cite
|
Sign up to set email alerts
|

Optimal profile for concave slopes under static and seismic conditions

Abstract: This study presents a methodology to determine the stability and optimal profile for slopes with concave cross section under static and seismic conditions. Concave profiles are observed in some natural slopes suggesting that such geometry is a more stable configuration. In this study, the profile of a concave slope was idealized by a circular arc defined by a single variable, the mid-chord offset (MCO). The proposed concave profile formulation was incorporated into a limit equilibrium–based log spiral slope st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…They show that logspiral profiles exhibit higher FoS than their planar counterparts for any value of c, and φ considered with the highest gain for inclinations midway and the vertical line, i.e., for OSA ∼ 4 + 2 . Since then, other researchers [9][10][11] have independently investigated the stability of concave profiles excavated in a uniform c-φ geomaterial, employing different methods, namely the slip line method [9], limit equilibrium methods [10], and the finite element method for the assessment of slope stability. They all reached the same conclusion concerning the superior stability of non-linear concave profiles.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…They show that logspiral profiles exhibit higher FoS than their planar counterparts for any value of c, and φ considered with the highest gain for inclinations midway and the vertical line, i.e., for OSA ∼ 4 + 2 . Since then, other researchers [9][10][11] have independently investigated the stability of concave profiles excavated in a uniform c-φ geomaterial, employing different methods, namely the slip line method [9], limit equilibrium methods [10], and the finite element method for the assessment of slope stability. They all reached the same conclusion concerning the superior stability of non-linear concave profiles.…”
Section: Introductionmentioning
confidence: 99%
“…They all reached the same conclusion concerning the superior stability of non-linear concave profiles. However, a key limitation of these studies is the assumption of a specific shape, either a circle [10] or a logspiral [8] or a curve stemming from the slip-line field theory and the associated characteristic equations [9], so that the shape claimed to be optimal is found as the shape associated to the highest stability number among curves belonging to a very restricted family. It is obvious that these profiles are instead sub-optimal and the shape of the truly optimal profile cannot be inferred from the aforementioned studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…oncave profiles have been presented as a way to optimize both the mechanical stability of slopes (Gray, 2013;Jeldes, et al, 2015aJeldes, et al, , 2015bSokolovskiĭ, 1960;Utili and Nova, 2007;Vahedifard et al, 2016aVahedifard et al, , 2016bZhang et al, 2017) and the water erosion resistance of slopes (Jeldes et al, 2015a;Rieke-Zapp and Nearing, 2005). Jeldes et al (2015a) suggested an approach to combine the mechanical and erosional benefits of concave slopes that includes (1) a procedure to obtain concave contours with the desired degree of mechanical stability, and (2) quantification of the effectiveness of those slopes in reducing erosion and sediment delivery.…”
mentioning
confidence: 99%